TINJAUAN YURIDIS TERHADAP MALPRAKTIK YANG DILAKUKAN OLEH PERAWAT PADA RUMAH SAKIT SWASTA (ANALISIS DARI PERSPEKTIF HUKUM PERDATA) - Shinta Permata Sari; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In the case of demage which often suffer bypatient consequenced the mistake and/orfailure by healthy persons (especially nurse) because didn’t do their practice based on profesionof standard, at this moment the society has been knowed and has consciousness completelytowards law in occur. So, if healthy of service which the patients received not optimal evenappeared the bad condition or has bee happened malpractice, the society would proposed claimto healthy service and healthy persons who worked in becaused of demage. More the malpracticecase doing by nurse, claimed responsibility of law on their action. The purpose from written thisscripsion are; The first, The Responsibility of Private A Nurse of The Private Hospital WhoDone Malpractice To Patient, The Second, The Eforts of Law Which Done by Patient Towards ANurse Done Malpractice. The conclusion are, The first, the responsibility of private a nurse ofprivate on malpractice done towards the patient is submit to contract agreement between a nurseand the hospital, which based on Pasal 1601 jo. 1601a KUHPerdata. If in contract agreementwhich made between the nurse with the private hospital said certainly if the nurse responsibilityaccording to law based on the mistake consequenced by doing them, so the nurse shouldresponsibility to paid that demage, based on Pasal 1365 jo. 1366 KUHPerdata, and Pasal 58 ayat(1) Undang-undang Kesehatan. The second, the patient could do the eforts of law, like litigationand non litigation. Writter suggest, The first, the government should made regulation shelf whichregulated about malpractice doing by healthy persons (included nurse), so that there is umbrellaof law especially about malpractice. The second, Undang-undang Keperawatan need to revisionbecaused nothing regulated about responsibility of nurse if they do the malpractice. LawEnforcer so that interpretation to used private punishment which included Kitab Undang-UndangHukum Perdata as one of instrument of law which still occured in Indonesia untill this moment.Key words: Malpractice – Nurse – Demage – Responsibility of Private – The Private Hospital